2013
DOI: 10.1007/s10120-013-0307-1
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pancreatic fistula formation according to ISGPF criteria after D2 gastrectomy in Western patients

Abstract: Background Limited information is available on the incidence of postoperative pancreatic fistula (POPF) after D2 gastrectomy with the strict use of the International Study Group of Pancreatic Fistula (ISGPF) criteria, particularly so in Western patients. Methods All patients who underwent gastrectomy for adenocarcinoma at the Karolinska University Hospital Huddinge from 2006 until June 2012 were identified via hospital records and reviewed for type of surgical procedure, postoperative morbidity, incidence, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The diagnostic criteria for POPF have not been uniformly defined in the field of gastric cancer surgery, and instead the criteria for pancreatic surgery, International Study Group on Pancreatic Fistula (ISGPF) criteria, have been applied after gastrectomy [16,17]. In this study, we aimed to evaluate the 267 ability of D-AMY to predict clinically problematic POPF.…”
Section: Definition Of Popfs and Treatmentsmentioning
confidence: 99%
“…The diagnostic criteria for POPF have not been uniformly defined in the field of gastric cancer surgery, and instead the criteria for pancreatic surgery, International Study Group on Pancreatic Fistula (ISGPF) criteria, have been applied after gastrectomy [16,17]. In this study, we aimed to evaluate the 267 ability of D-AMY to predict clinically problematic POPF.…”
Section: Definition Of Popfs and Treatmentsmentioning
confidence: 99%
“…Therefore, it has been shown that the incidence of complications after gastrectomy is directly related with the extent of the surgery. Additionally, pancreatic resection in association with gastrectomy has been shown to be an important and inevitable risk factor for POPF 5,7 . During the evaluation of POPF after gastrectomy, exclusion of these cases may help physicians to predict more accurate risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…A clinically significant grade B pancreatic fistula was present if there was any change in the postoperative management, for example if drains were either left in place more than 3 weeks or repositioned through endoscopic or percutaneous procedures. A grade C fistula corresponded to the occurrence of severe clinical repercussions requiring reoperation or lead to single or multiple organ failure and/or mortality attributable to the pancreatic fistula 1,5,10 . Severe POPF were regarded as the cases with grade B or C pancreatic fistula.…”
Section: Definition Of Popfmentioning
confidence: 99%
See 1 more Smart Citation
“…The excised portions included the head, neck and uncinate process of the pancreas, duodenum, distal stomach, proximal jejunum, gallbladder and common bile duct [10,11] . The tissue around the head of the pancreas and common hepatic duct, and the lymph nodes within the hepatoduodenal ligament were also resected.…”
Section: A T E R I a L A N D M E T H O D S 1 Clinical Datamentioning
confidence: 99%